2010
DOI: 10.3109/02841851003620366
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of local leakage of bone cement after percutaneous kyphoplasty and vertebroplasty

Abstract: Local leakage of bone cement was more common for percutaneous vertebroplasty compared with kyphoplasty (P<0.005). The most common sites of local leakage were perivertebral soft tissue and perivertebral vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 11 publications
4
39
1
6
Order By: Relevance
“…These results are similar to those in another study using CT, also reporting less leakage in BKP (49%) versus VP (87%). 50 Leakage into the perispinal vasculature was significantly less (P ϭ .028) for BKP. Meta-analyses of complications suggest that BKP results in fewer symptomatic cement leakages, which include embolism and spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those in another study using CT, also reporting less leakage in BKP (49%) versus VP (87%). 50 Leakage into the perispinal vasculature was significantly less (P ϭ .028) for BKP. Meta-analyses of complications suggest that BKP results in fewer symptomatic cement leakages, which include embolism and spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that a larger volume of bone cement achieved better correction effect (On-line Table). Nevertheless, increasing numbers of studies showed [22][23][24][25] that bone cement injection volume had no corre- lation with pain relief and had a positive correlation with bone cement leakage rate. In the clinic, many factors influenced the cement injection volume, such as the severity of osteoporosis, the degree of compression, the region of fracture, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Pensamos que esto es debido, fundamentalmente, a la relativa corta experiencia en el uso de cementos biológicos en estas técnicas y a que los grupos de tratamiento no serían comparables, ya que cada tipo de cemento estaría indicado en pacientes de características muy distintas. Las complicaciones más importantes de los procedimientos de refuerzo vertebral reflejadas en la literatura son 23 48 En cuanto a la fractura vertebral adyacente existe cierta controversia al respecto, ya que mientras que ciertos estudios aseguran que el endurecimiento vertebral es responsable directo de la aparición de las mismas, llegando a reportar un riesgo de entre el 10 y el 14%, dependiendo de las series 27 , en otros estudios se rechaza tal aseveración 8,11 , haciendo responsable de la misma al proceso patológico subyacente a la fractura, que en la mayoría de los casos es la osteoporosis. El resto de las complicaciones son excepcionales y su papel en la literatura es meramente anecdó-tico.…”
Section: Discussionunclassified
“…El riesgo de extravasación del cemento se encuentra, según las series, entre el 20-72'5% para la VP y el 1-49'2% para la CP, aunque en la mayoría de las series el riesgo para esta última suele ser menor al 7% 23,27 . Habitualmente la fuga de cemento suele ser asintomática, aunque, en función del espacio al que se produzca la extravasación, pueden aparecer complicaciones de mayor entidad e incluso mortales 23 . Las fugas de cemento se pueden dividir en tres tipos en función de la zona por la que sale el mismo 28,48 : 1.…”
Section: Discussionunclassified
See 1 more Smart Citation